2006
DOI: 10.1177/000313480607200908
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of Adhesion Formation and Shrinkage of Intra-Abdominal Prosthetics in a Rabbit Model

Abstract: Laparoscopic ventral hernia repair requires an intraperitoneal prosthetic; however, these materials are not without consequences. We evaluated host reaction to intraperitoneal placement of various prosthetics and the functional outcomes in an animal model. Mesh (n = 15 per mesh type) was implanted on intact peritoneum in New Zealand white rabbits. The mesh types included ePTFE (DualMesh®), ePTFE and polypropylene (Composix®), polypropylene and oxidized regenerated cellulose (Proceed®), and polypropylene (Marle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(17 citation statements)
references
References 24 publications
0
16
0
1
Order By: Relevance
“… 23 These are plagued with a multitude of complications ranging from contraction to erosion and evisceration. 24 To address this, surgeons have looked to bioprosthetics as a solution to overcome the disadvantages of synthetic prosthetics. While biologically derived or biological material–based non-synthetic devices have shown some success, their place in the operative theater has been limited to repair in which infection is present.…”
Section: Discussionmentioning
confidence: 99%
“… 23 These are plagued with a multitude of complications ranging from contraction to erosion and evisceration. 24 To address this, surgeons have looked to bioprosthetics as a solution to overcome the disadvantages of synthetic prosthetics. While biologically derived or biological material–based non-synthetic devices have shown some success, their place in the operative theater has been limited to repair in which infection is present.…”
Section: Discussionmentioning
confidence: 99%
“…Placement of ORC side facing the orbital soft tissue decreases but not prevent the adhesions between the mesh and the orbital soft tissue. Harrell AG et al (32), have evaluated the adhesion formation of intra-abdominal prosthetics in a rabbit model. They found that polypropylene mesh alone formed more adhesions with greater tenacity than Proceed mesh.…”
Section: Improvement Of All Preopertive Findingsmentioning
confidence: 99%
“…[11][12][13][14][15] The relative benefits of these different synthetic meshes with regard to adhesion formation, risk for infection, and outcomes have varied widely in different animal and human clinical studies. 9,13,[16][17][18][19] Furthermore, prospective data are lacking regarding the clinical benefits of these prostheses for ventral hernia repair, and no high-level evidence or comparative clinical data are currently available. Finally, lightweight polypropylene mesh with thinner-diameter polypropylene fibers and larger interstices is currently being used in both open and laparoscopic hernia repairs.…”
Section: Synthetic and Bioprosthetic Mesh Materialsmentioning
confidence: 99%